Endothelial-Derived miR-17∼92 Promotes Angiogenesis to Protect against Renal Ischemia-Reperfusion Injury - Chiba, Takuto (J Am Soc Nephrol, 2021)
BACKGROUND: Damage to the renal microvasculature is a hallmark of renal ischemia-reperfusion injury (IRI)–mediated AKI. The miR-17∼92 miRNA cluster (encoding miR-17, -18a, -19a, -20a, -19b-1, and -92a-1) regulates angiogenesis in multiple settings, but no definitive role in renal endothelium during AKI pathogenesis has been established. METHODS: Antibodies bound to magnetic beads were utilized to selectively enrich for renal endothelial cells from mice. Endothelial-specific miR-17∼92 knockout (miR-17∼92(endo−/−)) mice were generated and given renal IRI. Mice were monitored for the development of AKI using serum chemistries and histology and for renal blood flow using magnetic resonance imaging (MRI) and laser Doppler imaging. Mice were treated with miRNA mimics during renal IRI, and therapeutic efficacies were evaluated. RESULTS: miR-17, -18a, -20a, -19b, and pri–miR-17∼92 are dynamically regulated in renal endothelial cells after renal IRI. miR-17∼92(endo−/−) exacerbates renal IRI in male and female mice. Specifically, miR-17∼92(endo−/−) promotes renal tubular injury, reduces renal blood flow, promotes microvascular rarefaction, increases renal oxidative stress, and promotes macrophage infiltration to injured kidneys. The potent antiangiogenic factor thrombospondin 1 (TSP1) is highly expressed in renal endothelium in miR-17∼92(endo−/−) after renal IRI and is a target of miR-18a and miR-19a/b. miR-17∼92 is critical in the angiogenic response after renal IRI, which treatment with miR-18a and miR-19b mimics can mitigate. CONCLUSIONS: These data suggest that endothelial-derived miR-17∼92 stimulates a reparative response in damaged renal vasculature during renal IRI by regulating angiogenic pathways.